Trends in inpatient antiparkinson drug use in the USA, 2001–2012 - Crispo, James A. G. (Eur J Clin Pharmacol, 2015)
PURPOSE: Although therapeutic options and clinical guidelines for Parkinson’s disease (PD) have changed significantly in the past 15 years, prescribing trends in the USA remain unknown. The purpose of this population-based cohort study was to examine patterns of inpatient antiparkinson drug use between January 2001 and December 2012 in relation to clinical guideline publication, drug introduction/withdrawal, and emerging safety concerns. METHODS: A total of 16,785 inpatients receiving pharmacological treatment for PD were identified in the Cerner Health Facts database. Our primary outcome was standardized (age, sex, race, and census region) annual prevalence of antiparkinson drug use. We also examined antiparkinson medication trends and polypharmacy by age and sex. RESULTS: The most frequently prescribed antiparkinson drugs between 2001 and 2012 were levodopa (85 %) and dopamine agonists (28 %). Dopamine agonist use began declining in 2007, from 34 to 27 % in 2012. The decline followed publication of the American Academy of Neurology’s practice parameter refuting levodopa toxicity, pergolide withdrawal, and pramipexole label revisions. Despite safety concerns for cognitive impairment and falls, individuals ≥80 years of age demonstrated stable rates of dopamine agonist use from 2001 to 2012. Polypharmacy was most common in younger patients. CONCLUSIONS: Dopamine agonist use declined from 2007 to 2012, suggesting that increased awareness of safety issues and practice guidelines influenced prescribing. These events appear to have minimally influenced treatment provided to older PD patients. Antiparkinson prescribing trends indicate that safety and best practice information may be communicated effectively. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00228-015-1881-4) contains supplementary material, which is available to authorized users.